2009
DOI: 10.1016/s1726-4901(09)70066-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Timing and Dose of Rehabilitation Delivery on Functional Recovery of Stroke Patients

Abstract: There is a dose-dependent effect of rehabilitation on functional improvement of stroke patients for the first 6 months post-stroke, and earlier delivery of rehabilitation has lasting effects on the functional recovery of stroke patients up to 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 15 publications
2
43
0
8
Order By: Relevance
“…В двух исследованиях авторы сравни-вали раннюю мобилизацию в первые 3 сут после ин-сульта и позднюю, на 4-е сутки и позже. У пациен-тов из группы ранней мобилизации отмечалась меньшая степень инвалидизации, а также выше сте-пень подвижности и активности в повседневной жизни, в то же время уровень смертности не разли-чался в обеих группах [32][33][34][35][36][37][38][39]. Особого подхода тре-бует ранняя реабилитация пациентов с тяжелой со-путствующей патологией, в частности с хрониче-ской сердечной недостаточностью [40].…”
Section: сведения об авторахunclassified
“…В двух исследованиях авторы сравни-вали раннюю мобилизацию в первые 3 сут после ин-сульта и позднюю, на 4-е сутки и позже. У пациен-тов из группы ранней мобилизации отмечалась меньшая степень инвалидизации, а также выше сте-пень подвижности и активности в повседневной жизни, в то же время уровень смертности не разли-чался в обеих группах [32][33][34][35][36][37][38][39]. Особого подхода тре-бует ранняя реабилитация пациентов с тяжелой со-путствующей патологией, в частности с хрониче-ской сердечной недостаточностью [40].…”
Section: сведения об авторахunclassified
“…Studies in animal models have demonstrated the importance of rehabilitation intervention within the first week following stroke to maximize neurological recovery [29]. In humans, earlier delivery of rehabilitation has been associated with better functional recovery [29][30][31][32][33][88][89]. The duration of therapy is a topic of some debate because traditional belief has been that the majority of neurologic recovery occurs within the first 4 months following stroke [90].…”
Section: Better Treatment Planmentioning
confidence: 99%
“…Early initiation of stroke rehabilitation has in general been reported to be associated with greater functional recovery that is sustained at 1-year follow-up, 49 an effect that has been attributed, in part, to enhanced neuroplasticity in the early post-stroke period. 50 However, whether this advantage applies to aerobic training per se has not been ascertained.…”
Section: The Evidencementioning
confidence: 99%